The global prevalence of autism spectrum disorder: a comprehensive systematic review and meta-analysis - Nader Salari; Shabnam Rasoulpoor; Shna Rasoulpoor; Shamarina Shohaimi; Sima Jafarpour; Nasrin Abdoli; Behnam Khaledi-Paveh; Masoud Mohammadi (BMC, 2022)
Abstract Background Autism spectrum disorder (ASD) is one of the serious developmental disorders that is usually diagnosed below the age of three years. Although the severity of the disease's symptoms varies from patient to patient, the ability to communicate with others is affected in all forms of ASD. This study aimed to determine the prevalence of ASD in high-risk groups by continent. Methods The present study was conducted by systematic review and meta-analysis from 2008 to July 2021. Databases such as Science Direct, PubMed, Scopus, SID, Magiran, Web of Science (WoS), and Google Scholar from 2008 to July 2021 were searched to find related studies. Data were analysed using Comprehensive Meta-Analysis software (Version 2). Results A total of 74 studies with 30,212,757 participants were included in this study. The prevalence of ASD in the world was 0.6% (95% confidence interval: 0.4-1%). Subgroup analyses indicated that the prevalence of ASD in Asia, America, Europe, Africa and Australia was 0.4% (95% CI: 0.1-1), 1% (95% CI: 0.8-1.1), 0.5% (95% CI: 0.2-1), 1% (95% CI: 0.3-3.1), 1.7% (95% CI: 0.5-6.1) respectively. Conclusion ASD imposes a heavy health burden on communities around the world. Early detection of ASD can reduce the incidence of developmental disorders and improve patients' communication skills. Therefore, health policymakers need to be aware of the prevalence and increasing trend of ASD to implement appropriate planning and interventions to reduce its consequences.